2019
DOI: 10.1002/bjs.11110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative injection of superparamagnetic iron oxide particles on rates of sentinel lymph node dissection in women undergoing surgery for ductal carcinoma in situ (SentiNot study)

Abstract: Background: One-fifth of patients with a preoperative diagnosis of ductal carcinoma in situ (DCIS) have invasive breast cancer (IBC) on definitive histology. Sentinel lymph node dissection (SLND) is performed in almost half of women having surgery for DCIS in Sweden. The aim of the present study was to try to minimize unnecessary SLND by injecting superparamagnetic iron oxide (SPIO) nanoparticles at the time of primary breast surgery, enabling SLND to be performed later, if IBC is found in the primary specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
2
35
0
1
Order By: Relevance
“…In previous studies from our group, results have shown that a preoperative injection of SPIO can be extended to more than 30 days before surgery with equally high SLN detection rates [14,17,24], but this had not been tested with a reduced SPIO dose. It is now clearer that timeframe is probably more important than the dose itself.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies from our group, results have shown that a preoperative injection of SPIO can be extended to more than 30 days before surgery with equally high SLN detection rates [14,17,24], but this had not been tested with a reduced SPIO dose. It is now clearer that timeframe is probably more important than the dose itself.…”
Section: Discussionmentioning
confidence: 98%
“…Current SLNB might be on the way out. A recently published Swedish study showed a new promising approach to SLNB by using superparamagnetic iron oxide, enabling SLNB to be performed later only on those with invasive cancer after tumour resection and allowing up to 80% of women to avoid SLNB altogether 37 . Four ongoing trials, LORD, LORETTA, COMET and LORTIS are independently assessing active surveillance and/or endocrine therapy as an alternative non-inferiority treatment to low-risk DCIS 38 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The unique property of this tracer is that after injection, it remains in the lymph nodes for weeks and, unlike other tracers, allows for delayed SLN biopsy. 4 Patients with ductal carcinoma in situ (DCIS) undergoing mastectomy or large oncoplastic procedures can have Magtrace injected at the time of primary surgery but avoid SLN biopsy. Only the patients who upgrade to invasive disease require a return to the operating room for node excision, saving thousands of women per year the cost and complication risks associated with SLN biopsy.…”
Section: Futurementioning
confidence: 99%